Answer:
6.6%
Step-by-step explanation:
Answer:
64/49
Step-by-step explanation:
The applicable rules of exponents are ...
(a^b)^c = a^(bc)
(a^b)(a^c) = a^(b+c)
a^-b = 1/a^b
a^0 = 1
_____
Using these rules, we can simplify the given expression to ...
![\left(\dfrac{8\cdot 4\cdot 2}{8\cdot 7}\right)^2\times\left(\dfrac{8^0}{7^{-3}}\right)^3\times 7^{-9}\\\\=\dfrac{8^2}{7^2}\times(8^{0\cdot 3}\cdot 7^{3\cdot 3})\times 7^{-9}\\\\=\dfrac{64}{49}\times(8^07^{9-9})=\boxed{\dfrac{64}{49}}](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac%7B8%5Ccdot%204%5Ccdot%202%7D%7B8%5Ccdot%207%7D%5Cright%29%5E2%5Ctimes%5Cleft%28%5Cdfrac%7B8%5E0%7D%7B7%5E%7B-3%7D%7D%5Cright%29%5E3%5Ctimes%207%5E%7B-9%7D%5C%5C%5C%5C%3D%5Cdfrac%7B8%5E2%7D%7B7%5E2%7D%5Ctimes%288%5E%7B0%5Ccdot%203%7D%5Ccdot%207%5E%7B3%5Ccdot%203%7D%29%5Ctimes%207%5E%7B-9%7D%5C%5C%5C%5C%3D%5Cdfrac%7B64%7D%7B49%7D%5Ctimes%288%5E07%5E%7B9-9%7D%29%3D%5Cboxed%7B%5Cdfrac%7B64%7D%7B49%7D%7D)
Answer:
Kim will need to spend 67 minutes on her sixth ride
Step-by-step explanation:
Represent the number of minutes of her sixth ride by m.
Then the average number of minutes is
53 + 43 + 56 + 54 + 45 + m
---------------------------------------- = 53
6
Multiplying both sides of this equation by 6 yields
6(53 + 43 + 56 + 54 + 45 + m)
--------------------------------------------- = 6(53)
6
which simplifies to
251 + m
---------------- = 318
or 251 + m = 318. Subtract 251 from both sides to obtain the value of m:
m = 318 - 251 = 67
Kim will need to spend 67 minutes on her sixth ride to attain an average ride length of 53 minutes.i
Answer:
Step-by-step explanation:
4 1/2 - 2 5/8
4 4/8 - 2 5/8 = 1 and 7/8
i mean i guess you could also do this witho ut sol ving
4 4/8 - 21/8 --> 36/8 - 21/8
i dk it's si mplify not solve so here?
Answer:
pokemon
Step-by-step explanation: